Vimentin is a component of a complex that binds to the 5′‐UTR of human heme‐regulated eIF2α kinase mRNA and regulates its translation. Issue 5 (26th January 2013) - Chatterjee, Sangeeta; Panda, Amaresh C.; Berwal, Sunil K.; Sreejith, R.K.; Ritvika, Charu; Seshadri, Vasudevan; Pal, Jayanta K.
Abstract : The human heme‐regulated eIF2α kinase, also called the human heme‐regulated inhibitor (hHRI) is significantly up‐regulated particularly at the level of translation during stress. In this report we show that during lead‐stress, the regulation of hHRI mRNA translation is mediated through its 5′‐untranslated region (UTR) that interacts with specific trans‐acting factors. Further, vimentin has been identified as one of the trans‐acting factors that contribute to this regulation. Abstract : ► The hHRI 5′‐UTR is highly GC rich and has a complex secondary structure. ► The hHRI 5′ UTR acts as an inhibitor of its own translation by binding to cytoplasmic factors. ► Reduced binding of these factors during stress leads to up‐regulation of its translation. ► We have identified different mRNP complexes in K562 cells under normal and stress conditions. ► Among these, vimentin has been identified as a component of the hHRI mRNP complex.